A Cell of Origin Gene Signature Indicates Human Bladder Cancer Has Distinct Cellular Progenitors. (April 2014) - Dancik, Garrett M.; Owens, Charles R.; Iczkowski, Kenneth A.; Theodorescu, Dan
Abstract There are two distinct forms of urothelial (bladder) cancer: muscle‐invasive (MI) and nonmuscle invasive (NMI) disease. Since it is currently believed that bladder cancer arises by transformation of urothelial cells of the basal layer, bladder cancer stem cells (CSCs) have been isolated based on expression markers found in such cells. However, these CSCs have only been identified in MI tumors raising the intriguing hypothesis that NMI tumor progenitors do not arise from the basal compartment. To test this hypothesis, we carried out genome‐wide expression profiling of laser capture microdissected basal and umbrella cells, the two most histologically distinct cell types in normal urothelium and developed a cell of origin (COO) gene signature that distinguishes these. The COO signature was a better predictor of stage and survival than other bladder, generic, or breast CSC signatures and bladder cell differentiation markers in multiple patient cohorts. To assess whether NMI and MI tumors arise from a distinct progenitor cell (DPC) or common progenitor cell, we developed a novel statistical framework that predicts COO score as a function of known genetic alterations (TP53, HRAS, KDM6A, and FGFR3) that drive either MI or NMI bladder cancer and compared this to the observed COO score of the tumor. Analysis of 874 patients in five cohorts established the DPC model as the best fit to the available data. This observation supports distinct progenitor cells in NMI and MI tumors and provides a paradigm shift in our understanding of bladder cancer biology that has significant diagnostic and therapeutic implications. Stem Cells2014;32:974–982